ANALISIS STRATEGI PT. TELEKOMUNIKASI INDONESIA, TBK MENGHADAPI PERSAINGAN GLOBAL - Setyowati, Erlina Nur’aini; Ekananda, Mahjus; Mubarok, Faizul (Jurnal Ilmiah Ekonomi Bisnis, 2024)
The significant contribution of information and communication technology (ICT) to Indonesia's economic growth, surpassing the national GDP growth rate. This growth is attributed to strategic determinations made by companies considering both internal and external factors. The study aims to analyze these influences on PT. Indonesian Telecommunications' competitive strategy to enhance competitiveness. Employing quantitative descriptive research, it utilizes Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices. Primary and secondary data were collected through purposive and snowball sampling techniques, involving employees of PT. Telekomunikasi Indonesia, Tbk. Data collection methods included questionnaires and secondary data from company archives and statistical sources. SWOT analysis, IFE, and EFE methods were applied, revealing PT. Telekomunikasi Indonesia, Tbk's adeptness in leveraging strengths, addressing weaknesses, seizing opportunities, and mitigating threats. IFE and EFE scores averaged 3.44 and 3.15 respectively, indicating an aggressive growth stance. Positioned favorably, the company is poised for expansion and heightened growth amidst global competition.